Object Salience in the Division of Labor: Experimental Evidence - Raveendran, Marlo; Puranam, Phanish; Warglien, Massimo (Management Science, 2016)
When we engage in the process of division of labor, there are typically multiple alternatives, but insufficient knowledge to choose among them. Under such conditions, we propose that not all alternatives are equally likely to be pursued. In particular, when we engage in the process of division of labor for novel and nonrepetitive production, we argue that we display a tendency to perceive and select object-based task partitions over activity-based partitions. We experimentally investigate how the salience of objects over activities manifests itself in individuals and groups engaged in division of labor for the assembly of strongly or weakly decomposable products. We draw implications for organization design as well as the impact of technological change on organizations. This paper was accepted by Jesper Sørensen, organizations.